2020
DOI: 10.1111/1462-2920.14886
|View full text |Cite
|
Sign up to set email alerts
|

Methane oxidation in anoxic lake water stimulated by nitrate and sulfate addition

Abstract: Methanotrophic bacteria play a key role in limiting methane emissions from lakes. It is generally assumed that methanotrophic bacteria are mostly active at the oxic-anoxic transition zone in stratified lakes, where they use oxygen to oxidize methane. Here, we describe a methanotroph of the genera Methylobacter that is performing high-rate (up to 72 μM day −1 ) methane oxidation in the anoxic hypolimnion of the temperate Lacamas Lake (Washington, USA), stimulated by both nitrate and sulfate addition. Oxic and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
70
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(85 citation statements)
references
References 88 publications
(110 reference statements)
6
70
1
Order By: Relevance
“…The chromium-augmented treatment showed only a 1.61-fold increase for the high methane as compared to near atmospheric methane treatment (6 ppm). The sequence analysis of the microbial community from lake Biwa, Japan [3,56], stratified eutrophic Swiss lakes [57] and Lacamas lake in Washington, USA [58] showed Type I methanotroph dominances, similarly to our findings in this study.…”
Section: Methanotrophic Community Abundance In Response To Heavy Metalssupporting
confidence: 89%
“…The chromium-augmented treatment showed only a 1.61-fold increase for the high methane as compared to near atmospheric methane treatment (6 ppm). The sequence analysis of the microbial community from lake Biwa, Japan [3,56], stratified eutrophic Swiss lakes [57] and Lacamas lake in Washington, USA [58] showed Type I methanotroph dominances, similarly to our findings in this study.…”
Section: Methanotrophic Community Abundance In Response To Heavy Metalssupporting
confidence: 89%
“…The most abundant methanotroph of Lacamas Lake, a seasonally stratified lake, is a Methylobacter species; it was detected in the oxic water column in the winter and in the microoxic oxycline and the anoxic hypolimnion in the summer (van Grinsven et al, 2019). In order to be able to further study the response of this methanotroph to different concentrations of oxygen and other electron acceptors, an enrichment culture was established.…”
Section: Resultsmentioning
confidence: 99%
“…Lacamas Lake, the source of the material used for our enrichment culture, contained uncultured Methylobacter species thriving in the oxic and anoxic water columns as well as in the microoxic oxycline (van Grinsven et al, 2019). Incubations with water column samples revealed that these bacteria oxidized large amounts of methane (72 µM day −1 ) under anoxic conditions in the stratified summer water column, stimulated by the addition of both nitrate and sulfate (van Grinsven et al, 2019), but were also naturally present in the oxic, methane-depleted winter water column. Phylogenetic analysis showed that the Methylobacter species of the Lacamas Lake summer and winter water columns and incubations grouped closely together with the Methylobacter species that dominated the enrichment culture (i.e., 96-99% similarity; Figure 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…consumption not only in oxic but also in hypoxic and even anoxic niches (9)(10)(11)(12), even though the mechanisms for such activity remain poorly understood, given the essential role of dioxygen in methane oxidation catalyzed by methane monooxygenase (MMO). The observations on the dominant nature of Methylobacter have also been supported by results from microcosm incubation experiments in which Methylobacter performed as the most competitive species, especially under low dioxygen tensions (13,14).…”
mentioning
confidence: 99%